An embodied perspective on judgements of written reflective practice for professional development in Higher Education. Issue 1 (2nd January 2016) - Leigh, Jennifer
Abstract : This paper gives an embodied perspective on the use of judgements of reflective practice and reflective writing for professional development in Higher Education. Programmes for professional development in Higher Education and recognition processes for academics have become prevalent in the UK and internationally. These programmes and processes often assume, implicitly or explicitly, development or evidencing as a 'reflective practitioner' through pieces of reflective writing which is then judged against competencies or attainments. However, this focus on reflective practice and reflective writing is not always critical, and does not examine the different theoretical and practical interpretations of what it means to reflect, or the impact of assessing such reflections. Taking an embodied stance allows a new view into a contested area that is more habitually connected with cognitive rather than corporeal processes.